2016
DOI: 10.1515/nbec-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Can β-D-Glucan Protect Oat Seeds against a Heat Stress?

Abstract: Plants have evolved to live in environments where they are often exposed to different stress factors. Being sessile, they have developed specific mechanisms that allow them to detect precisely environmental changes and respond to complex conditions, minimizing damage while conserving valuable resources for growth and reproduction. The cell wall polysaccharide β-D-glucan observed in some species of Poales can determine responses to various environmental factors in specific plant developmental stages. It is loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Two MTAs (S3B_768483613 and S3B_768483625) within 15 bp range were found in the gene, TraesCS3B01G526100, which is annotated as 1,3-beta-glucanase. Havrlentová et al (2016) suggested this gene as having a possible protective mechanism role in oat during heat stress conditions. Five markers on chromosome 6B (S6B_238165759, S6B_238165760, S6B_238165774, S6B_238165775, S6B_238165776) all within 17 bp range were detected in multiple environments suggesting the genetic stability of these MTAs.…”
Section: Discussionmentioning
confidence: 99%
“…Two MTAs (S3B_768483613 and S3B_768483625) within 15 bp range were found in the gene, TraesCS3B01G526100, which is annotated as 1,3-beta-glucanase. Havrlentová et al (2016) suggested this gene as having a possible protective mechanism role in oat during heat stress conditions. Five markers on chromosome 6B (S6B_238165759, S6B_238165760, S6B_238165774, S6B_238165775, S6B_238165776) all within 17 bp range were detected in multiple environments suggesting the genetic stability of these MTAs.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the concentration of avenanthramides in response to salinity stress in CBF3 transgenic oat demonstrated that these compounds might have a potential role in enhancing abiotic stress tolerance in oats [154]. Havrlentova et al [155] suggested that oats with higher β-D-glucan content may have thicker and, therefore, more insulating cell walls, better adapted to heat stress conditions. The same conclusion between higher content of β-D-glucan and greater cell wall thickness has been reported in barley [156].…”
Section: Abiotic Stress Resistancementioning
confidence: 99%
“…Initial observations have suggested that oat genotypes disposing of higher β-D-glucans content are more resistant to pathogen manifestations caused by parasitic organisms being “inhibited” in their pathogen manifestations by thicker cell wall in which β-D-glucans are produced in higher amounts [ 19 ]. In our previous work it was proven that β-D-glucans in the oat grain can protect the grain against high temperature [ 22 ]. It this work, it was expected that oat genotypes with higher β-D-glucans content may be more resistant to artificial inoculation with FC and FG .…”
Section: Discussionmentioning
confidence: 99%
“…Rapid cell wall reinforcement can reduce success of pathogen’s penetration. Such enhancements occur due to the accumulation of β-(1-3)-glucan [ 19 , 20 ], β-D-glucans [ 21 ] and proteins in the area between the cell wall and the cell membrane [ 22 ]. The gel-layer formed by β-D-glucans in the cell wall may also act as a defensive wall protecting the cell from invasion by fungi but also providing a potential signal system to indicate when such an attack is under the way [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation